Hydrophobic packing in T4 lysozyme probed by cavity-filling mutants. - Karpusas, M (1989)
To probe the nature of the hydrophobic cores of proteins and to test potential ways of increasing protein thermostability, an attempt was made to improve the packing within T4 bacteriophage lysozyme by engineered amino acid replacements. Two mutations, Leu-133----Phe and Ala-129----Val, which were designed to fill the largest cavities that exist in the folded structure of the native protein, were constructed. The mutant proteins have normal activities and their thermal stabilities are marginally lower than that of wild-type lysozyme. Crystal structure analysis of the mutant proteins shows that the introduced amino acids are accommodated with very little perturbation of the three-dimensional structure. Incorporation of the more bulky hydrophobic residues within the core of the protein is expected to provide an increase in hydrophobic stabilization, but this is seen to be offset by the introduction of strain. Inspection of the mutant structures shows that in each case the introduced amino acid side chain is forced to adopt a non-optimal dihedral angle X1. Strain is also observed in the form of bond angle distortion and in unfavorable van der Waals contacts. The results illustrate how the observed core structures of proteins represent a compromise between the hydrophobic effect, which will tend to maximize the core packing density, and the strain energy that would be incurred in eliminating all packing defects. The results also suggest that mutations designed to increase protein stability by filling existing cavities may be effective in some cases but are unlikely to provide a general method for increasing protein stability.